If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + -1(3x + 7) = 8 + (4x + 1) Reorder the terms: 9x + -1(7 + 3x) = 8 + (4x + 1) 9x + (7 * -1 + 3x * -1) = 8 + (4x + 1) 9x + (-7 + -3x) = 8 + (4x + 1) Reorder the terms: -7 + 9x + -3x = 8 + (4x + 1) Combine like terms: 9x + -3x = 6x -7 + 6x = 8 + (4x + 1) Reorder the terms: -7 + 6x = 8 + (1 + 4x) Remove parenthesis around (1 + 4x) -7 + 6x = 8 + 1 + 4x Combine like terms: 8 + 1 = 9 -7 + 6x = 9 + 4x Solving -7 + 6x = 9 + 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. -7 + 6x + -4x = 9 + 4x + -4x Combine like terms: 6x + -4x = 2x -7 + 2x = 9 + 4x + -4x Combine like terms: 4x + -4x = 0 -7 + 2x = 9 + 0 -7 + 2x = 9 Add '7' to each side of the equation. -7 + 7 + 2x = 9 + 7 Combine like terms: -7 + 7 = 0 0 + 2x = 9 + 7 2x = 9 + 7 Combine like terms: 9 + 7 = 16 2x = 16 Divide each side by '2'. x = 8 Simplifying x = 8
| a+2b+3c=455 | | X^4-9x^2-36=0 | | -1/3X-1/2 | | 5x^3+2x^2-3x+2=0 | | -1/10X1/2 | | -3/4X1/3 | | 4/9x-2/5 | | 1/2(8x-14)=-13 | | x^2+y^2-10x=0 | | -18=-4x+31-6x+27 | | 2x+8/5=(2X/3) | | 2x-6=3x-9-4x | | 2(2x-3)+3(4-x)=-(x+1) | | 4x^2-4=8 | | 3x^2-7-1=0 | | -8i^14= | | 3.5=-y+6.3 | | 4.3t-2.1t-2.3t=7.6 | | 12+7=10x+13 | | -3=(z/5)-2 | | (5i+2)(4-3i)-(2-i)(6i-7)= | | 3u-12=24 | | 4x+(2x-5)=1 | | 20-9x=37 | | 21-5x=8 | | 2(5/9)=y-3(2/3) | | 1/4(2x+40)=3x | | (2y-1)=-10(y-5) | | 9x+9=14x-5 | | 6x+9=7x-2 | | 9(x-1)=5x+15 | | 8x-4=6x+8x+8 |